Penelaahan Pemanfaatan Tagetes erecta L. (Marigold) secara Tradisional dalam Bidang Pertanian dan Obat-Obatan di Indonesia - Raihandhany, Reza; Hanifah, Dini Siti (Fakultas Biologi Universitas Gadjah Mada, 2025)
Tagetes erecta also known as marigold is a domesticated plant which traditionally still in use today, both in agricultural and health aspects due to its usefulness and benefits that contains active compounds in the whole plant parts. In the agricultural sector, Tagetes erecta is widely used as a pest agent and disease control in integrated farming practices, while in the health sector, this plant is extensively used in traditional medicine, particularly in several regions in Indonesia. This study reviews the benefits related to Tagetes erecta, notably in agricultural and health sectors, in order to obtain in-depth information regarding their huge potential that has been and has not been optimally in use. Exploring data for this paper using literature studies on related journals by looking for the similarities, differences, point of view by previous research, as well as future prospects, both in local and global utilization. The literature study is also conducted to achieve study objectives. The results found that Tagetes erecta is a plant with enormous benefits, from the roots to flowers. It has distinctive characteristics of active compounds compared to other similar species. However, study on the utilization of Tagetes erecta can lead to optimizing the management of integrated farming systems, increasing food security, maintaining the local wisdom of the community, and providing knowledge about the importance of marigold. Hopefully, the utilization of Tagetes erecta in daily life able to achieve a healthy and sustainable ecosystem to achieve prosperous life in the future.